2020
DOI: 10.1080/17508975.2020.1745741
|View full text |Cite
|
Sign up to set email alerts
|

Lighting in the third dimension: laser scanning as an architectural survey and representation method

Abstract: This paper proposes tridimensional (3D) laser scanning to architects and lighting designers as a lighting enquiry and visualization method for existing built environments. The method constitutes a complement to existing lighting methods by responding to limitations of photometric measurements, computer simulation and HDR imagery in surveying and visualizing light in actual buildings. The research explores advantages and limitations of 3D laser scanning in a case study addressing a vast, geometrically complex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…While both imaging luminance measurement and indoor 3D reconstruction have been extensively presented with conventional digital cameras in prior research, their integration remains to be demonstrated. Laser scanning and HDR imaging have been proposed for surveying and visualizing lighting in indoor spaces, since current lighting measurement methods are too limited for 3D design (Rodrigue et al, 2020). The study also showed that the characteristics of the existing lighting need to be understood by architects and lighting designers in order to redesign the lighting.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…While both imaging luminance measurement and indoor 3D reconstruction have been extensively presented with conventional digital cameras in prior research, their integration remains to be demonstrated. Laser scanning and HDR imaging have been proposed for surveying and visualizing lighting in indoor spaces, since current lighting measurement methods are too limited for 3D design (Rodrigue et al, 2020). The study also showed that the characteristics of the existing lighting need to be understood by architects and lighting designers in order to redesign the lighting.…”
Section: Related Workmentioning
confidence: 99%
“…The study also showed that the characteristics of the existing lighting need to be understood by architects and lighting designers in order to redesign the lighting. However, when Rodrigue et al (2020) performed such measurements, they only transmitted the colour values for visual inspection of the 3D point cloud, as the values were obtained from an uncalibrated scanner camera and not from a luminance-calibrated camera. In addition, their research revealed that 2D luminance photometry alone is not appropriate for surveying an indoor space with six degrees of freedom, and image locations must be managed manually.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, photogrammetry can perform poorly when measuring the 3D geometry of smooth, mono-colored, and uniform surfaces [ 26 ]. Luminance measurement applications require accurate radiometric data, and the use of 3D luminance measuring in design would be beneficial not only for lighting designers but also for architects [ 27 ]. However, indoor 3D luminance measurements made with a terrestrial laser scanner have not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…As the sensors are increasingly applicable for HDR imaging [ 3 ], the utilization of such HDR imaging-capable TLS instruments for producing a 3D point cloud with luminance information is a topical development issue. While the use of TLS for lighting design via luminance measuring has been suggested in earlier research [ 27 , 28 ], a solution employing the TLS images for luminance measuring is missing, since Rodrique et al [ 27 ] utilized a separate imaging luminance photometer and they did not register the luminance values into a 3D luminance point cloud. Instead, they assessed the geometry and luminance measuring as separate entities.…”
Section: Introductionmentioning
confidence: 99%